Klausa Relatif Bahasa Karo - Yuanita, Arie (Universitas Negeri Surabaya, 2023)
This research aims to explain the position of core nouns in relative clauses in theKaro language, the types of relative clauses in the Karo language, and strategiesfor relativizing relative clauses in the Karo language. The research method usedin this research to collect data is the library method while analyzing the datausing the collection method using techniques for direct elements. From theresearch results it is shown that the position of the core noun of the Karolanguage relative clause is classified as a postnominal form, namely the relativeclause comes after the core noun. However, apart from being in postnominal form,there are several relative clauses in the Karo language that are also in prenominalform, that is, the relative clause comes before the main noun. There are two typesof relative clauses in the Karo language, namely restrictive relative clauses andnonrestrictive clauses. These two types of clauses are quite often found in relativeclauses in the Karo language. In connection with the relativity strategy, Karo language clauses apply a permutation strategy. With the permutation strategy, it can be seen that postnominal Karo language relative clauses cannot be expanded because the clauses become ungrammatical, while prenominal Karo language relative clauses can be expanded and are grammatical.